Finance Research Productivity and Influence - Borokhovich, Kenneth A.; Bricker, Robert J.; Brunarski, Kelly R.; Simkins, Betty J. (Journal of Finance, 1995)
This study examines differences in finance research productivity and influence across 661 academic institutions over the five year period from 1989 through 1993. We find that 40 institutions account for over 50% of all articles published by 16 leading journals over the five year period; 66 institutions account for two-thirds of the articles. Influence is more skewed with as few as 20 institutions accounting for 50% of all citations to articles in these journals. The number of publications and publication influence increase with faculty size and academic accreditation. Prestigious business schools are associated with high publication productivity and influence.